Social Capital Development for Sustainable Community: Case Study on Sekolah Master Indonesia (SMI) - Fitriani Fazrin; Yusuf Mulyana (Green Publisher Indonesia, 2024)
Community sustainability often comes to a halt at the stage of community organizational change, especially in the context of leaders. Further studies on the focus on empowering community organizations need to be strengthened to support sustainable communities. The case study method was used in this study with the research subject of community regeneration of the Sekolah Master Indonesia (SMI) located in Depok. The results of the study show that even though SMI has managed to survive for 24 years, it has not let go of the community's concerns in the sustainability of community leadership. SMI's success in carrying out components that support community sustainability has not covered the chaos when there is a change in leadership. The focus on strengthening the capacity of organizational resources is important to anticipate from the beginning, so that the empowerment of community members is felt thoroughly by every community member who can be the successor in community regeneration.